Phytoremediation of Zinc (Zn) in Leachate-Contaminated Soil Using Vetiver (Chrysopogon zizanioides) with Compost Addition - Ameviana Fitri Noveira; Endah Dwi Hastuti; Yulita Nurchayati (Indonesian Journal of Environmental Management and Sustainability, 2026)
Soil contamination by zinc (Zn) derived from landfill leachate poses significant ecological risks, particularly in regions with limited waste management capacity such as Indonesia. The Jatibarang landfill in Semarang has reported soil Zn concentrations exceeding the Ecological Soil Screening Level, highlighting the need for sustainable remediation strategies. This studyevaluated the stability of vetiver (Chrysopogon zizanioides)-based phytoremediation under varying plant densities and compost amendment in leachate-contaminated soil. A two-month greenhouse experiment was conducted using a 2 × 2 factorial completely randomised design with two planting densities (one and three plants per polybag) and two compost treatments (with and without compost). Parameters observed included soil Zn concentration, removal efficiency, bioconcentration factor (BCF), translocation factor (TF), plant biomass, and soil pH, analysed using two-way ANOVA (? = 0.05). All treatments significantly reduced soil Zn concentrations from 174.41 mg/kg to 49.33-52.17 mg/kg, corresponding to removal efficiencies of 70.09-71.72%, with no statistically significant differences among treatment combinations. Zinc accumulation occurred predominantly in the roots, reflected by higher root BCF values and TF values generally below one, confirming phytostabilisation as the dominant remediation mechanism. These findings indicate that vetiver-based phytoremediation provides a stable and reliable strategy for controlling Zn mobility in landfill leachate-contaminated soils, supporting its application as a sustainable soil management approach.